The Influence of Compensation, Motivation and Work Discipline on Employee Performance at the Harbormaster's Office and Class I Port Authority of Banjarmasin - Leki, Rofinus; Faisal, Said Ali; Kadir, Abdul; Audah, Ali; Fatih, Hardika Muhammad (Universitas Hang Tuah, 2025)
This study aims to analyze the influence of work motivation, compensation, and work discipline on employee performance at the Port Authority and Harbormaster Office (Kesyahbandaran dan Otoritas Pelabuhan) Class I Banjarmasin. The research is based on the importance of improving employee performance as a key factor in ensuring the organization’s success in delivering optimal public services. A quantitative approach was employed using a survey method with questionnaires distributed to selected employees as respondents through purposive sampling. Data analysis was carried out using multiple linear regression with F-test, t-test, and coefficient of determination (R²). The findings indicate that work motivation, compensation, and work discipline have a positive and significant effect on employee performance, both simultaneously and partially. The coefficient of determination (R²) of 0.978 shows that the three independent variables explain 97.8% of employee performance variation, while the remaining 2.2% is influenced by other factors outside the model. Partially, work discipline is the most dominant variable influencing employee performance. The study concludes that improving work discipline, supported by adequate motivation and compensation, significantly enhances employee performance. The practical implication suggests that management should strengthen disciplinary policies, reward systems, and motivational programs to optimize employee performance.